Labral augmentation with ligamentum capitis femoris: presentation of a new technique and preliminary results. Issue 1 (16th January 2018) - Weidner, Jan; Wyatt, Michael; Beck, Martin
ABSTRACT: Preservation of an intact labrum and reconstruction of a deficient or worn acetabular labrum are accepted techniques in modern hip surgery. If the remaining labrum is very thin, its intact tip can be preserved and its volume restored with a ligamentum teres graft. Technique and preliminary results of this augmentation technique are presented. Labral augmentation was performed in 16 hips (11 rights) in 16 patients (7 males, mean age 29 years) during surgical dislocation for treatment of femoroacetabular impingement. The acetabular index, lateral center edge angle, asphericity angle and acetabular retroversion index were determined on preoperative X-rays and magnetic resonance imaging. The pre- and postoperative Merle d'Aubigné and Postel score (MdA) was calculated and the Oxford Hip Score (OHS) obtained after 1 year. There were seven Grade 1 and nine Grade 0 hips (Tönnis classification). Mean lateral center edge was 29°. The mean acetabular index was 1.85°. Mean asphericity angle was 62.5°. Mean acetabular retroversion index was 23.4%. Mean MdA improved from 14.5 preoperatively to 17 at 1 year ( P < 0.0001). Mean OHS after 1 year was 42. Previous surgery was a risk factor for inferior results: OHS was 44.5 in hips without versus 26 in hips with previous surgery. Mean MdA improved from 15 to 17.5 in patients without previous surgery versus 14 to 16 for the group with previous surgery. Augmentation of the labrum using ligamentum teres shows good clinical results after 1 year. Patients with previous hip surgery had inferior results.